Motivation Matters: Profiling Indigenous and Non-Indigenous Students’ Motivational Goals - Magson, Natasha R.; Craven, Rhonda G.; Nelson, Genevieve F.; Yeung, Alexander S.; Bodkin-Andrews, Gawaian H.; McInerney, Dennis M. (The Australian Journal of Indigenous Education, 2014)
This research explored gender and cross-cultural similarities and differences in the motivational profiles of Indigenous Papua New Guinean (PNG) and Indigenous and non-Indigenous Australians. Secondary students (N = 1,792) completed self-report motivational measures. Invariance testing demonstrated that the Inventory of School Motivation (McInerney, Yeung, & McInerney, 2001) measure was invariant across both gender and Indigenous and non-Indigenous groups. Structural equation modelling (SEM) results explicated that males were significantly more performance orientated than females in all three groups examined; however, the disparity between genders was most apparent in non-Indigenous Australians. Diverging from previous findings with non-Indigenous students, the current study found that PNG and Australian Indigenous males endorsed mastery goals more strongly than Indigenous females. In contrast, non-Indigenous females were more mastery orientated than non-Indigenous males. Finally, the two Indigenous groups endorsed social goals more strongly than the non-Indigenous Australians. The current findings highlight the importance of assessing gender and group differences, as broad statements relating to student motivation do not appear to be applicable in all cultural contexts.